Teachers and Students Perceptions of Grammar Teaching in Curriculum 13 - Sakina, Rahma (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
This research is aimed at investigating teachers’ and students’ perceptions on the role of grammar in English teaching learning and how grammar is taught in curriculum 13. The research employed a qualitative descriptive design. The data were gathered through questionnaire and interview. The participants involved in this research were three English teachers and thirty students of grade X and XI in a private senior high school in Bandung. The findings revealed that the teachers and students had the same view about the importance of grammar both in language teaching learning and communication. Although the majority of them agreed that the knowledge of grammar is beneficial in both speaking and writing activities, there were a few of them who disagreed its importance in speaking. Furthermore, teachers and students in this research were aware that grammar in the curriculum 13 is more appropriate to be taught under Communicative Language Teaching (in which grammar is taught integrated into communicative activities, inductively, and with contextualized grammar practice) than under Grammar Translation Method (in which grammar is taught in separate lesson, in deductive approach, and emphasizing practice of patterns). From the findings, it was recommended that grammar needs to be taught in the current curriculum using Communicative Language Teaching method.